Teacher’s Strategy in Dealing with Disruptive Behavior from a Student’s Perspective - Bekti Ningsih; Endang Fauziati; Yeny Prastiwi; Laili Etika Rahmawati (STAI Hubbulwathan Duri, 2023)
Schools provide understanding to students to avoid disruptive behavior. Teachers have strategies to deal with disruptive student behavior in the classroom. This study aims to describe teacher strategies in dealing with student disruptive behavior and reveal students' preferences for teacher strategies in dealing with disruptive behavior of the first grade at a public elementary school in Baki. This type of research is qualitative using a case study approach in an elementary school so that the subject of the study is teachers and students. This research data are information about teacher strategies in dealing with student disruptive behavior and students’ preferences toward teacher strategies in dealing with disruptive behavior in the classroom. The data sources used are students and teachers. Data collection techniques used were observation and interviews. Meanwhile, the data were analyzed using Miles, Huberman, and Saldana’s model consisting of data collection, data reduction, data presentation, and drawing conclusions. The results showed that teachers used several strategies to deal with students' disruptive behaviour, including classroom management, taking individual approaches, behavior management, understanding student characteristics, and teaching social skills. The strategies that students prefer are classroom management, individual approach, and behavior management. Disruptive behavior of students during learning can be reduced if the teacher has an effective strategy and that strategy becomes the student's preference.